2013 delmar healthcare drug handbook - George, Spratto R.; Woods, Adrienne L. (Delmar Cengage Learning, 2013)
Feel confident in your knowledge of over 770 FDA-approved drugs with this handbook as your trusrtworthy and accurate drug information resource. This vital resource clearly describes the uses, side effects, contraindications, actions, and dosages for each drug covered. Each entry also provides information for effective drug administration and improved patient communication